2021
DOI: 10.3390/ijerph182212103
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Health-Related Quality of Life of Entrepreneurs. A Cross-Sectional Study

Abstract: Background: Quality of life is one of the most important conceptual categories in many scientific fields and socio-economic practices. In the authors’ opinion, the assessment of the overall quality of life and the health-related quality of life of private entrepreneurs deserves particular attention. Until now, quality of life and its determinants in entrepreneurs have been investigated by few authors. The aim of this study was to identify and assess the key determinants of quality of life and its health-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…It means that they obtain recognition from government agencies, employees and family members, have time to travel, and own assets. These findings are further strengthened through the study by Puciato, Rozpara, Bugdol, Borys, and Słaby [35] who stated that family involvement is able to strengthen women's entrepreneurial performance. However, Yusof et al, [63] reported that quality of life, which includes income, level of education, and involvement in the economy of rural communities, especially FELDA, is still low.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…It means that they obtain recognition from government agencies, employees and family members, have time to travel, and own assets. These findings are further strengthened through the study by Puciato, Rozpara, Bugdol, Borys, and Słaby [35] who stated that family involvement is able to strengthen women's entrepreneurial performance. However, Yusof et al, [63] reported that quality of life, which includes income, level of education, and involvement in the economy of rural communities, especially FELDA, is still low.…”
Section: Methodsmentioning
confidence: 89%
“…The quality of life refers to a person's standard of living and their socioeconomic status [35]. Suradi [3] defines the quality of life based on two aspects.…”
Section: Life Competencies and Quality Of Lifementioning
confidence: 99%
“…The notion of entrepreneurship was connected with quality of life (Delfmann et al, 2014;Puciato et al, 2021). The importance of entrepreneurship is being underlined in the literature not only for the economic growth (Fritsch & Mueller, 2007) but also for employment growth (Van Stel & Suddle, 2008;Porter, 2019).…”
Section: New-business Formation Factorsmentioning
confidence: 99%